Etika Akademik dalam Tradisi Ilmiah di Kalangan Akademisi IAIN Ar-raniry - Abdul Wahid (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
IAIN Ar-Raniry is an educational institute that carries on both knowledge  and Islamic missions. Both aspects are gauge to measure the development of  knowledge performed by the institute. Islamic scholar ethic is another  measurement for academic commitment on religious values. For that, the  development of knowledge at the institute can be gauged from the productivity of  the academic, a side of the quality. While the commitment to preserve and to  implement the Islamic ethics, can be witness from the originality of their works.  To the best of writer‟s observation, the level of productivity seems relatively  under expectation, while the ethic on the other hand, is seemingly preserved by  academic of the Institute.